PELAKSANAAN MANAJEMEN SUMBERDAYA AIRTANAH METODE SUMUR RESAPAN UNTUK KONSERVASI AIRTANAH PADA AKIFER DANGKAL (SHALLOW AQUIFER) DI WILAYAH DAERAH KHUSUS IBUKOTA JAKARTA - Bambang Sutedjo HS; Isrofah Isnaeni Nugro (Jurnal Ilmiah MTG, 2009)
Development of physical build progress at DKI Jakarta area is increase pass by increase all the sector to make changes fungtion of landform like than forest fungtion, farms fungtion make real estate area, hotels and industries area. And than recharge area to decrease that is all, maked to changes of hydrology cycle is that decrease water rainfall to infiltrated to increase of runoff water.Hydrology and some factor to affected groundwater static water level at the shallow aquifer and value of infiltration capacity, and rainfall at The DKI Jakarta area, to make total artificial recharge to be needed of conservation methode at shallow aquifer. Lower plain of Jakarta Coastal added at North part of West Java, with has spread from West part of Java to East following North Coastal from West Java until Cirebon City, with wide plus minus 40 Km. In the regional North Coatal plain added with some high area and sub – basin. Jakarta area is a part sedimentation sub – basin and they call of Ciputat sub – basin, the West part this basin bodered by Tangerang High, at the East part by Rengasdengklok High and at the South part gradational to Bogor Antikinorium.Generally of DKI Jakarta area has to investigation by Soekardi (1985(, Nippon Koei et. Al (Cisadane River Basin Development Feassibility / CRBDFS, 1987), with to make differeanted of Jakarta Groundwater Basin to four part that is Coastal area are North of Tangerang – Jakarta – Bekasi, , Terraces area at the central art basin, the Tertiary bedrock with small production and volcano slope area of Salak and Pangrango. Thickness of Quartenary sediment in the Central Basin to interpretative than 250 meters until 300 meters, and less thickness to South West – South – South East from Jakarta about 25 meters to 50 meters (Warsito, 1985), because closed by contack with Tertisru sediments.From the analysis are finally of infiltration capacity (after balanced point) at the DKI Jakarta area is variatiun. Finally of infiltration capacity is lower value (0,01 Cm/ minutes) they are at the location two, three, four, and the higher (1,98 Cm / minutes) at the location 71. Perbandingan of smaller value and higher value is 198. In the geography position higher value at the South part, and smaller value at the North part.